Pengelolaan Arsip Dan Kode Klafikasi Jabatan Pada Institut Agama Islam Negeri ( IAIN) Ternate - Naemudin, Rusdi (Sekolah Tinggi Agama Islam Babussalam Sula, 2021)
The purpose of this study was to determine archive management and job classification codes at IAIN Ternate, this study used a qualitative descriptive method. As for the results of the research conducted on archive management at IAIN Ternate, it turned out to be in the form of archives in the form of work letters and other archives, management of outgoing and incoming mail by applying an agenda book, management or archive management that changes in the arrangement of the archives. , receive archives and storage then record the archive in the agenda book after that the archive is stored according to its clarification. Archives at IAIN are also seen as still less than optimal due to the unavailability of a special room for archiving, as well as a shortage of archivist human resources and the feasibility of archiving at IAIN Ternate, far from the possibility of forming an archival institution. While the classification code at the Ternate State Islamic Institute, is very useful for ensuring and effectiveness as a means of communication between organizational units and work units, as well as between work units at the Ternate State Islamic Institute.